TANTANGAN MANAJEMEN SUMBER DAYA MANUSIA DALAM PENDIDIKAN DI ERA SOCIETY 5.0 - Asrulla Asrulla; Samsu; Tuti Indriyani; Firdaus Jeka (Jurnal Genta Mulia, 2024)
One of the important resources in Islamic education management is human resources. The importance of human resources needs to be realized by all parties that the quality of educators will greatly support the success of school management. However, the rapid advancement of technology poses a challenging task in the field of education. Nevertheless, qualified educators still play a crucial role in the success of a school organization. In fact, the rapid advancement of technology will go hand in hand with the improvement of educator quality, which becomes the pioneer of educational progress itself. In educational institutions, human resource management is crucial to be implemented. Without good human resource management, an organization, including educational institutions, will generally struggle to achieve its goals. Human resource management is the most important element in management because human resources are the first element in management before other elements. The role of human resource management in educational institutions certainly contributes significantly to improving the quality of education, as quality education comes from qualified individuals who manage it. However, in the course of human resource management in education, there are many challenges that need to be addressed with concrete solutions in order to develop more effective human resources, which will have implications for educators' ability to adapt to the rapid development of the times.